Demography of a confined elephant population and the potential consequence of translocation: the case of Sweetwaters Game Reserve, Kenya - Ogola, Patrick; Omondi, Patrick (Pachyderm, 2005)
Between February and July 2001 the demography of the elephant population in Sweetwaters GR in the Laikipia District of Kenya was studied with particular reference to age structure, family group size and family unit composition. Since 1989 this populations has been confined effectively confined by fences. Data in this study was compared with that from an earlier 1992-1993 study. (Omondi et al, 1993) Observations largely confined to waterpoints and salt licks focused on identifying individuals and family units in order to assess the population prior to a planned translocation of bulls and family units to Meru NP. The 120 elephant observed includes 100 in 12 cow-calf groupings and 20 independent bulls ranging in age from 10 years of age upwards. The cow calf grouping accounted for 59% of the observations. The structure of these groups included 9.6% calves of one year or younger and 49.6’ females aged over 12 years. About 94% of the females ’were observed to associate closely with cales thought to be their offspring’ which suggests that this population is increseing at a high rate. The number of groups has increased, but the average group size has decreased since the 1992-1993 study which suggests and population which feels secure of unthreatened. Shortly after this study members of a number of family units identified during the observations were moved as a groups and most of the independent bulls were removed from this population and translocated in Meru NP. The study population indluded was 59 females, and 61 males: 23 of the females were calves and subadults, and 36 were mature cows while 54 of the males were calves and subadults and 7 were mature bulls. After identified groups and bulls had been translocated the remaining g population consisted of 64 animals, 27 females and 37 males: 8 of the females were calves and subadults and 19 were mature cows, while of the 37 males 36 were calves or subadults and 1 was a mature bull. The population dynamics of the remaining population will be interesting to observe.